Lingualand Media Development to Improve Beginning Reading Abilities of 5-6 Year-Old Children - Miftah Dilla; Ria Novianti; Rita Kurnia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study developed the digital learning media